Meningkatkan Kepercayaan Diri dan Penguasaan Materi Agama Siswa Melalui Kegiatan Kultum Setelah Sholat Zuhur Berjamaah - Sugianto Sugianto; Julianne Kamelia Riza; Alex Pujosakti (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research analyzes the implementation of kultum activities (seven-minute lectures) after congregational noon prayers to increase students' self-confidence and mastery of Islamic religious material at SMP Muhammadiyah 1 Jombang. The research method is a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research showed that the cult activities went well and increased students' self-confidence and mastery of Islamic religious material. Students' self-confidence increases because they are used to speaking in public, while their mastery of the material increases because students have to study and understand the material before delivering it. Obstacles faced, such as students who are not used to speaking in public, annoying audiences, and errors in reciting verses, can be minimized by providing guidance, motivation, and ongoing evaluation. The implementation of this cult activity is a real effort to realize the school's vision and mission, as well as forming positive characters in students through instilling values such as love for Allah SWT, self-confidence, hard work, mastery of religious material, independence, responsibility, honesty, trustworthiness, respect, courtesy, leadership, justice, kindness, humility, tolerance, peace, and unity.